Retour sur un Eternel Droit à Debat : Le Droit à l’Avortement. Pour quelle position? (African Journal of Law and Politics, 2023)
The right to life is part of the broader principle of human dignity. It now occupies a prominent and visible place in human rights instruments. In addition to this right, throughout the world a principle is developing parallel or even contrary to the unavailability of the human body (one of the inclinations of which is the prohibition of harming the life of others): the principle of self-disposition that some would describe as the very principle of our modernity". Between these two fundamental ideals is a right that is debated, the right to abortion. The issue of abortion continues to divide jurisprudence and tear doctrine apart. Since each society has its own culture and legal tradition, the legal status of the unborn child is not unanimous among States. In this case, one may wonder if the notion of the right to life varies according to the cultural environment in which life develops? Or why do some states accept the right to abortion and others do not? The answer to such a question is not obvious and may lie in the degree of perception of the notion of human dignity in each society. This plunges the right to life into a legal and cultural pluralism. The purpose of this article is to provide analyses of the right to abortion in cases of risks during pregnancy and non-existence of risks on the other hand